Risk factors associated with cutaneous anthrax outbreaks in humans in Bangladesh - Sukanta Chowdhury; Md. Saiful Islam; Md. Saiful Islam; Najmul Haider; Najmul Haider; Muhammad Belal Hossain; Muhammad Belal Hossain; Md. Ashraful Alam; Md. Ahmad Raihan Sharif; M. Salim Uzzaman; Mahbubur Rahman; Mahmudur Rahman; et al. (Frontiers Media S.A., 2024)
ObjectivesTo determine the risk factors associated with cutaneous anthrax infection in humans.MethodsDuring 2013-2016, we investigated total 26 anthrax outbreaks across the country. We additionally conducted a case-control study to identify risk factors by recruiting four controls for each enrolled case. Adjusted odds ratios (aOR) and 95% confidence intervals (CI) were estimated to identify risk factors using multivariate logistic regression.ResultsOver the study period, a total of 1,210 suspected cutaneous anthrax cases were identified in seven districts of Bangladesh. Most of the cases (61%, n = 744) were detected from Meherpur district. Cases were detected over the year, with the peak number of outbreaks occurring in May. The overall attack rate of suspected cutaneous anthrax cases for 16 outbreaks was 20%, with the highest rate occurring among individuals aged 40-49 years. Persons who had a cut injury (aOR 19.04, CI: 4.08-88.86), weighed raw meat (aOR 5.73, CI: 3.03-10.83), mixed bones and meat (aOR 4.64, CI: 3.03-7.09), observed livestock slaughtering (aOR 2.86, CI: 2.02-4.04), had direct contact to an anthrax suspected livestock (aOR 2.68, CI:1.61-4.45), slaughtered livestock (aOR 2.29, CI: 1.3-4.02), and who did not wash hands with soap and water after direct contact (aOR 2.57, CI: 1.89-3.5) were more likely to develop cutaneous anthrax than people who did not have these exposures.ConclusionPrior cut injuries on exposed body areas during meat handling and slaughtering of sick livestock were identified as potential risk factors for cutaneous anthrax, highlighting the importance of preventing the slaughter of sick animals. However, stopping slaughtering sick livestock, handling meat and livestock by-products to reduce anthrax exposures from livestock to humans may be difficult to achieve given the associated financial incentives in Bangladesh. Interventions such as hand washing with soap during slaughtering and processing meat can be targeted to affected communities to ameliorate some risk.